Os Simpsons e o Brasil : imagens de um olhar estrangeiro em “Blame it on Lisa” - Peres, Simone Oliveira Vieira (2013)
With the object of analysis the episode "Blame it on Lisa" series of U.S. "The Simpsons", this study discusses the process of images construction on Brazil, from view and foreign relations of identity and otherness, strangeness and identifications. The choice this episode lies in the fact describes the Simpsons family visit to Brazil and thus constructs a narrative based on criticisms and stereotypes about the characters and the Brazilian culture. Launched in 2002, the episode caused quite a stir among viewers and Brazilian government. The development of this research will be guided mainly in Cultural Studies, through analysis of the episode, from literature and other content (movies, books, newspapers, magazines, etc.) that give us clues to understanding how images on the country, from one perspective "foreign", built up marked by stereotypes. Starting from the unrest caused by the images reproduced in the country foreign films, we discuss how this gaze is directed to “ourselves", how the process of constructing this Brazil‟s portrait and the size of the dialogue between the gaze of the "other" and the native, having in view of the identities of Brazil and Brazilian forged by "ourselves."